The Role of Knowledge in Computer Collaborative Learning Research - De Nardis, Evelina (European Journal of Multidisciplinary Studies, 2022)
The aim of this paper is to describe the most significant theoretical frameworks concerning Computer Collaborative Learning Research (CSCL) on the light of Web 2.0 supports. The term Web 2.0 embraces a range of ‘social’ technologies and tools that enable users to create, publish and share digital contents within both new and existing social networks. Technologies such as blogs, wikis, podcasts and file sharing services are increasingly being used to support learning and teaching within the higher education sector (see Hughes, 2009; Kennedy et al., 2009). The implications of collaborative interactions within the socio-constructivism approach are examined. Harasim (2012) defines online collaborative learning as characterized by interactive group knowledge-building processes. This aspect implies that students participate actively by monitoring different levels of learning while they are collaborating with teacher and pairs. The computer supported collaborative learning research (CSCL) community focus on the role of technology considered as a tool through which students and teacher make sense of the world and negotiate meaning. Many researches about CSCL environments concerns the role of teacher in allowing social and significant interactions among all group members. Three factors drive the change from teacher-centered to centered learning approach, the shift from individual to group learning and from contiguous to asynchronous distributed learning groups. All of these aspects imply changes in educational institutions based on social construction of knowledge and competence-based learning. Through the years of competence based approaches have proved to be a critical tool in human resources management and computer collaborative research.
Keywords: social- interaction, Collaborative Learning Research, constructivism.